CSA/CIS Bundle 1: Sustainable financing for off-grid solar irrigation: Using big data to provide user-centric financial solutions to scale end-to-end irrigation technologies and services for small-scale farmers in Zambia - Vitalite, Lupiya; Links, Lima (Accelerating Impacts of CGIAR Climate Research for Africa, 2021)
Our business partnership and project brings together 3 of Zambia’s most forward-thinking enterprises, ready to disrupt the African agricultural market in order to transform the way business is done for every African farmer. While our project focuses on Zambia, our solutions can be scaled to create opportunities for transparency, inclusivity, and success across Sub-Saharan Africa and beyond. Founded in Zambia, Lupiya, Vitalite and Lima Links are enterprises with strong track records in being first to market with agricultural technology and financing solutions that have innovation, impact and potential for scale at the very heart of their design. We will use the project funding, together with our own significant financial and non-financial resources, to demonstrate our capacity to solve the biggest obstacles preventing smallholders from growing and protecting their farming businesses, and permanently lifting themselves out of poverty. Specifically we will develop a fully functioning credit scoring method for smallholders that we will then refine, scale, and make core to Lupiya’s agri finance product and service. We will leverage Lima Links 111,000+ farmer user base to survey farmers and design a farmer-centric agri loan product ready to take to market (MVP). We will pre-finance procurement of 150 off-grid irrigation pumps and realize the sale and distribution of 250 pumps to farmers on pay-as-you-go payment plans. We will engage Lima Links farmer user base to generate demand for 2,000+ additional irrigation pump/CSA technology sales. In parallel we will pursue Lima Links existing partnership with ZMD to provide climate information services via Lima Links USSD platform